If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying F(x) = ln(ln(8x)) Multiply F * x xF = ln(ln(8x)) Remove parenthesis around (8x) xF = ln(ln * 8x) Reorder the terms for easier multiplication: xF = ln(8ln * x) Multiply ln * x xF = ln(8lnx) Remove parenthesis around (8lnx) xF = ln * 8lnx Reorder the terms for easier multiplication: xF = 8ln * lnx Multiply ln * lnx xF = 8l2n2x Solving xF = 8l2n2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8l2n2x' to each side of the equation. -8l2n2x + xF = 8l2n2x + -8l2n2x Combine like terms: 8l2n2x + -8l2n2x = 0 -8l2n2x + xF = 0 Factor out the Greatest Common Factor (GCF), 'x'. x(-8l2n2 + F) = 0Subproblem 1
Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0Subproblem 2
Set the factor '(-8l2n2 + F)' equal to zero and attempt to solve: Simplifying -8l2n2 + F = 0 Reorder the terms: F + -8l2n2 = 0 Solving F + -8l2n2 = 0 Move all terms containing x to the left, all other terms to the right. Add '-1F' to each side of the equation. F + -1F + -8l2n2 = 0 + -1F Combine like terms: F + -1F = 0 0 + -8l2n2 = 0 + -1F -8l2n2 = 0 + -1F Remove the zero: -8l2n2 = -1F Add '8l2n2' to each side of the equation. -8l2n2 + 8l2n2 = -1F + 8l2n2 Combine like terms: -8l2n2 + 8l2n2 = 0 0 = -1F + 8l2n2 Simplifying 0 = -1F + 8l2n2 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Solution
x = {0}
| x(x+14)=66 | | 0.3x-0.6+1.0x= | | .2x-1.4=4.9x+1.3 | | 0.15p-3.5=1 | | 7500+155f=92440 | | X^4=60 | | -4+2y=-16 | | .7x-1.4=1.3x+2.1 | | (9x^5)5=9 | | 7500+155f=0 | | (y-7)+11= | | .5x-1.6=4.8x+2.8 | | 50/3=75/x | | .06(y-9)+.16y=.02y-.9 | | 2p+12=54 | | 0.5(5-7x)=8-(4+6) | | .50x+.35(50)=49.5 | | -7/15-(-11/15) | | 2(x-4)=5(x+2) | | 5z/6=35 | | x/4-6=x/7-3 | | 4b^3=74 | | 2x+2(x-2)=20 | | 3x=7/4 | | -2(y+6)=y+2y | | 2x+4(-7x+15)=-96 | | -5*3/8 | | d=f | | -17+x+17+1=2 | | 9y^2+48y+15=0 | | 5(4k+14)=10k-2(k-7) | | [3x-1]+6= |